Analisis Gaya Bahasa Puisi “Senja Merindu” Karya Rainy Zikri - Nadia Mutiara Hafiz; Wina Melani (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This research aims to examine the language style in the poem "Senja Merindu" by Rainy Zikri. The problem that will be raised in this research is related to the language style contained in it so that it can create aesthetics in the work. The language style used is believed to have an important role in conveying the feelings and meaning that the writer wants to convey to the reader. The method applied is analytical descriptive with a literature study approach. The object of this research is the poem "Senja Merindu" by Rainy Zikri which has a distinctive language style. The results of the analysis show that this poetry contains melancholic, romantic and lyrical language styles. The melancholic style is seen in the theme of longing, romantic in the nuances of love, and lyrism is reflected in the use of deep poetic language. It is hoped that this research can become a reference for further research related to language style in poetry.